2005
DOI: 10.1007/s10708-004-1930-5
|View full text |Cite
|
Sign up to set email alerts
|

Wal-Mart and Aldi: Two Retail Giants in Germany

Abstract: Wal-Mart entered the German market at the end of 1997 but is still running at a loss in its 92 stores. This article tests the hypothesis that there are two main reasons for Wal-Mart's problems in Germany. First of all, Wal-Mart is competing against very strong and well established deep discounters, especially Aldi. Secondly, there is the difference between the so-called Wal-Mart culture and German customer values. So far, Wal-Mart has not managed to close this gap or create a positive image in Germany. The fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…: this affected store sales densities. We re‐emphasise that Factor 1 in our analysis indicated that store products were the prime evaluative factor (see again Gerhard & Hahn, ), even though E‐Mart patrons also displayed generally higher satisfaction levels regarding convenience and accessibility. At E‐mart, products were seen as more authentically Korean and the Korean food shopper is well educated on quality and authenticity.…”
Section: Analysis Of Store Performance Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…: this affected store sales densities. We re‐emphasise that Factor 1 in our analysis indicated that store products were the prime evaluative factor (see again Gerhard & Hahn, ), even though E‐Mart patrons also displayed generally higher satisfaction levels regarding convenience and accessibility. At E‐mart, products were seen as more authentically Korean and the Korean food shopper is well educated on quality and authenticity.…”
Section: Analysis Of Store Performance Resultsmentioning
confidence: 63%
“…Also, for all three retail chains, diversification into overseas markets has involved a mixture of successes and failures. For example, WalMart entered and soon left Germany – where Gerhard and Hahn () found that locals preferred familiar products offered by Aldi. Also, Carrefour entered and left England and Wales and Tesco entered and left the USA.…”
Section: Retailing and Globalisationmentioning
confidence: 99%
“…In addition to this, no money is spent on attractive stores, floors, or lighting; ads always look the same because no marketing experts are employed; few retailing experts are employed -new ideas are tested at three stores, and if deemed a success, are copied in other stores; and there are no storage rooms, the goods being sold from the boxes on plain shelves. The average stores size is about 800 square metres, and for this space there are only 4-5 employees (Gerhard and Hahn, 2005). This devotion to keeping prices low is clearly appreciated by the customers, as Figure 7.4 demonstrates, it is the prime reason that people shop at Aldi, followed by best value and best special offers (and can likely be largely applied to other similar discounters, ie.…”
Section: Figure 73 : Felt Inflationmentioning
confidence: 99%
“…Retail literature also helps establish some patterns of change (ie. Wrigley and Lowe, 1996, Heinberg, 2001, Popp, 2004, and Gerhard and Hahn, 2005. The large stores of the Griine Wiese and the new Arena demonstrate that there are some retail changes occurring in Lahr, namely taking away the focus on the inner city as the main location of retail activity, which is occurring in many German cities (Heineberg, 2001).…”
Section: Germanymentioning
confidence: 99%
See 1 more Smart Citation